Socio-demographic indicators of alcohol dependence in patients treated for addiction in a post-industrial city - Marcin Kozak; Magdalena Piegza; Piotr Ścisło; Karina Badura-Brzoza; Piotr Wacław Gorczyca (Nofer Institute of Occupational Medicine, 2019)
Background The aim of the study was to evaluate the influence of the place of living on the prevalence of the alcohol dependence syndrome (ADS) and to find its possible connections with socio-demographic data within a post-industrial city with a population > 100 000 inhabitants. Material and Methods The study was carried out in 2004-2012 on a group of 431 patients living in Bytom with diagnosed ADS treated either in psychiatric wards or in outpatient psychiatric clinics. The patients' gender, age, employment, marital status, level of education and the fact of living in a given town district were analysed. The majority of the demographic data was obtained from the City Office. Results The study demonstrated the influence of the place of living, age, gender, level of education and employment on the prevalence of ADS in a post-industrial city. Conclusions Alcohol addicts who seek treatment are predominantly men > 40 years of age, with low education, mostly unemployed, living in the urbanized districts within the city center or the post-industrial area of the city, which are the areas with the highest risk of ADS. Living in a suburban neighborhood may protect against alcohol addiction due to the lower risk of exposure to environmental factors contributing to the prevalence of ADS. Additional protective factors include at least secondary education and paid employment prospects. The neighborhood of people with ADS has a particularly devastating effect on women, who are more likely to become addicted in such environments. Med Pr. 2019;70(2):221-8